Probe on wireless voice communication system of coal mine based on ZigBee - XU Xiao-xiao; QU Guang-xiang; HUANG Yan-qiu; CAI Yuan (Gong-kuang zidonghua, 2013)
For problem that existing voice communication systems usually use wired communication mode, which cannot guarantee reliability of communication when an accident happens, a kind of wireless voice communication system based on ZigBee technology was proposed. The hardware and software design schemes of wireless voice communication node were described in detail. Reception rate and RSSI were tested under laboratory environment when terminal nodes were in different distances. The test result showed when communication distance between nodes is more than 60 m, packet loss rate is increasing, while RSSI decreases with increasing of distance between nodes. Thus distance between base stations is decided as 60 m, and coverage radius of the base station is as 60 m.